Solvent-pair surfactants enabled assembly of clusters and copolymers towards programmed mesoporous metal oxides - Wenhe Xie; Yuan Ren; Fengluan Jiang; Xin-Yu Huang; Bingjie Yu; Jianhong Liu; Jichun Li; Keyu Chen; Yidong Zou; Bingwen Hu; Yonghui Deng (Nature Communications)
Abstract Organic-inorganic molecular assembly has led to numerous nano/mesostructured materials with fantastic properties, but it is dependent on and limited to the direct interaction between host organic structure-directing molecules and guest inorganic species. Here, we report a “solvent-pair surfactants” enabled assembly (SPEA) method to achieve a general synthesis of mesostructured materials requiring no direct host-guest interaction. Taking the synthesis of mesoporous metal oxides as an example, the dimethylformamide/water solvent pairs behave as surfactants and induce the formation of mesostructured polyoxometalates/copolymers nanocomposites, which can be converted into metal oxides. This SPEA method enables the synthesis of functional ordered mesoporous metal oxides with different pore sizes, structures, compositions and tailored pore-wall microenvironments that are difficult to access via conventional direct organic-inorganic assembly. Typically, nitrogen-doped mesoporous ε-WO3 with high specific surface area, uniform mesopores and stable framework is obtained and exhibits great application potentials such as gas sensing.